2016
DOI: 10.1039/c6qo00161k
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of trifluoromethylthiolated azacalix[1]arene[3]pyridines from the Cu(ii)-mediated direct trifluoromethylthiolation reaction of arenes via reactive arylcopper(iii) intermediates

Abstract: Using azacalix[1]arene[3]pyridines and their high valent organocopper(II) and (III) complexes as probes, arene C-H bond trifluoromethylthiolation was investigated. While arylcopper(II) compounds appeared almost inert, arylcopper(III) compounds reacted efficiently with a nucleophilic trifluoromethylthiolating reagent. Under mild conditions, azacalix[1]arene[3]pyridines underwent the regioselective Cu(ClO 4 ) 2mediated one-pot trifluoromethylthiolation reaction with Me 4 NSCF 3 to afford low-rim functionalized m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 65 publications
(42 reference statements)
0
16
0
Order By: Relevance
“…4‐( tert ‐Butyl)‐1‐methyl‐2‐[(trifluoromethyl)sulfinyl]benzene (3d′): Colorless liquid. 54 % (14.2 mg).…”
Section: Methodsmentioning
confidence: 99%
“…4‐( tert ‐Butyl)‐1‐methyl‐2‐[(trifluoromethyl)sulfinyl]benzene (3d′): Colorless liquid. 54 % (14.2 mg).…”
Section: Methodsmentioning
confidence: 99%
“…The obtained polymers showed no homocoupling defects and relatively good molecular weights (up to 10 kg mol −1 ) . Recent studies revealed that the Cu‐catalyzed C−H activation reactions proceed through organometallic C‐Cu intermediates . In the mechanism of Pd‐catalyzed direct arylation, the Cu species have two roles.…”
Section: Resultsmentioning
confidence: 99%
“…5 Since seminal works in the late nineties on polyazacalixarenes, [6][7][8][9][10] this family has been growing to incorporate trypticene moieties, 11,12 pyridine units, 13,14 and covalently-bonded metallic centers conferring unusual reactivity. [15][16][17][18][19][20] Noteworthy, ACA macrocycles were valorized for carbon dioxide uptake, 21,22 fullerene or anions complexation [23][24][25] and demonstrated to be relevant as hole-and spin-containing architectures. 26,27 In 2013, the azacalixphyrin (ACP, Figure 1) was reported as the only known "azacalixarene-like" derivative introducing four oxidized tetraaminobenzene units that promote a stable bis-zwitterionic ground electronic state.…”
Section: Introductionmentioning
confidence: 99%
“…Heteroatom-bridged calixarenes are an evolved class of calixarene macrocycles , in which the introduction of a bridging heteroatom in lieu of a methylene link provides additional features such as (i) the tuning of the cavity size and of the conformation (e.g., 1,3-alternate structure), (ii) new redox properties, and (iii) conjugation between the units of the macrocyclic oligomer. , Beyond the wide range of heteroatom-containing calixarenes developed during the past decades, azacalixarenes (ACA) demonstrated an undeniable versatility regarding structure–property shaping . Since seminal works in the late 1990s on polyazacalixarenes, this family has been growing to incorporate trypticene moieties, , pyridine units, , and covalently bonded metallic centers conferring unusual reactivity. Noteworthy, ACA macrocycles were valorized for carbon dioxide uptake , and fullerene or anion complexation and demonstrated to be relevant as hole- and spin-containing architectures. , In 2013, the azacalixphyrin (ACP, Figure ) was reported as the only known “azacalixarene-like” derivative introducing four oxidized tetraaminobenzene units that promote a stable bis-zwitterionic ground electronic state. Consequently, ACP can be viewed as a masked conjugated azacalixquinone. Its aromatic core involving 18 π-electrons confers to the ACP a strong absorption at ca.…”
Section: Introductionmentioning
confidence: 99%